GE_GERICHTE P/15537/2018 vom 9. Oktober 2019 - GE Cour de justice (2019)
PLAINTE PÉNALE;DÉLAI;DÉNONCIATION CALOMNIEUSE;INFRACTIONS CONTRE L'HONNEUR | CPP.310.al1.leta; cpp.310.al1.letb; CPP.310.al1.letc; CP.173; CP.303; CP.52; CP.31